Pengaruh Realisasi Belanja Modal, Fiscal Stress, Produk Domestik Regional Bruto (PDRB) Terhadap Kemandirian Keuangan Daerah (Studi Empiris Pada Pemerintah Daerah Kabupaten/Kota Di Provinsi Kalimantan Timur) - Rinaldi; Nuryasman MN (Jurnal Ekonomi, 2013)
The goal of the research is to analyse function relates to effects of capital expenditure, fiscal stress, GRDP changes to regional East Kalimantan's financial independence as simultaneously or partial as well. The research objects are capital expenditures, total local own revenues and total local revenues as stated in the financial operation statement in Indonesia. The degree of fiscal decentralization was used as an indicator of the new regencies' financial independence. The ratio of own local revenues and total local revenues was used to measure the degree of fiscal decentralization. This study uses secondary data from panel data for 4 (four) years from 2006 to 2009 from 13 districts/cities in the Indonesia division. The data analysis method used in this study is Multiple Linear Regression by using the application program SPSS version 17. Data was obtained from the Supreme Audit Board (BPK) of East Kalimantan Province and the Central Bureau of Statistics (BPS) of East Kalimantan Province. The data analyzed in this study are compiled from reports Actual Revenue and Expenditure (Budget). The results showed that the Capital Expenditures, Fiscal Stress and GRDP simultaneously significant effect on the Independence of Financial District/City in East Kalimantan Province. Partially Capital Expenditures no significant but positive effect, Fiscal Stress no significant but positive effects, while the GRDP has a significant and positive impact on Independence Financial District/City in East Kalimantan province.